Structure-function and industrial relevance of bacterial aminopeptidase P - Omar, Muhamad Nadzmi; Abd Rahman, Raja Noor Zaliha Raja; Muhd Noor, Noor Dina; Latip, Wahhida; Knight, Victor Feizal; Mohamad Ali, Mohd Shukuri (MDPI AG, 2021)
Aminopeptidase P (APPro, E.C 3.4.11.9) cleaves N-terminal amino acids from peptides and proteins where the penultimate residue is proline. This metal-ion-dependent enzyme shares a similar fold, catalytic mechanism, and substrate specificity with methionine aminopeptidase and prolidase. It adopts a canonical pita bread fold that serves as a structural basis for the metal-dependent catalysis and assembles as a tetramer in crystals. Similar to other metalloaminopeptidase, APPro requires metal ions for its maximal enzymatic activity, with manganese being the most preferred cation. Microbial aminopeptidase possesses unique characteristics compared with aminopeptidase from other sources, making it a great industrial enzyme for various applications. This review provides a summary of recent progress in the study of the structure and function of aminopeptidase P and describes its various applications in different industries as well as its significance in the environment.